Removal of remazol red dye in batik wastewater using natural coagulant of moringa seeds - Ulfa Arisca Yuniawati; Maya Rahmayanti (Jurusan Kimia FMIPA Universitas Lampung, 2023)
Remazol red dye in batik wastewater can cause damage to the aquatic environment and is toxic. This study aims to reduce the concentration of remazol red dye and COD content in batik wastewater by bio-coagulation. The natural coagulant used in this study was moringa seeds. The content of coagulant functional groups in Moringa seeds was characterized using a Fourier Transform Infrared (FTIR) spectrophotometer. Biocoagulation was carried out on variations in the acidity of batik wastewater, i.e., at pH 2,3,4,5, and 6. The results of the FTIR characterization of papaya seeds after biocoagulation showed a shift in the wave numbers of the OH, N=N, and C-O groups. The optimum pH for the biocoagulation process of remazol red dye occurs at pH 4 with a % reduction of remazol red dye of 91.24 % and a decrease in COD value of 71.13 %. Keywords: remazol red, coagulation, wastewater, batik, Moringa seeds